NUMERICAL SIMULATION OF THE INTERACTION OF A REGULAR WAVE AND A SUBMERGED CYLINDER - Teixeira, P. R. F. (Revista de Engenharia Térmica, 2009)
A numerical simulation of the interaction between a regular wave and an immersed horizontal cylinder, whose axis is 3-radius deep, perpendicular to the direction of the wave propagation, is presented in this paper. The numerical model uses the semi-implicit two-step Taylor- Galerkin method to integrate Navier-Stokes equations in time and space. Arbitrary lagrangean-eulerian formulation is employed to describe the free surface movement. The free surface elevations near the cylinder and in some gauges along the channel, as well the spectrum distribution, are compared with experimental ones, and good agreement is obtained. The analysis shows that the viscous effects only affect the area that is very close to the cylinder.